Magnetic resonance imaging flow quantification of non-occlusive excimer laser-assisted EC-IC high-flow bypass in the treatment of complex intracranial aneurysms - Brockmann, Carolin; Groden, Christoph; Neumaier-Probst, Eva (Clinical neuroradiology, 2012)
The patency of a bypass plays an important role in the postoperative recovery of patients especially when dealing with complicated intracranial aneurysms. In this study two-dimensional phase contrast magnetic resonance angiography (PC-MRA) was used to measure cerebral blood flow in 23 patients before extracranial-intracranial high-flow bypass surgery using the excimer laser-assisted non-occlusive anastomosis (ELANA) technique and in 15 patients following surgery. The results showed that PC-MRA is a suitable technique for assessing bypass patency and that with the ELANA technique the bypass has the capability of compensating the blood flow of an occluded internal carotid artery (ACI) in cases of complex aneurysms.
Published online: 3 December 2011
Gesehen am 24.07.2018